1991
DOI: 10.1056/nejm199111143252001
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Emergency Medical Resuscitation — Are Continued Efforts in the Emergency Department Justified?

Abstract: In general, continued resuscitation efforts in the emergency department for victims of cardiopulmonary arrest in whom prehospital resuscitation has failed are not worthwhile, and they consume precious institutional and economic resources without gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(86 citation statements)
references
References 30 publications
2
79
0
5
Order By: Relevance
“…The need for protracted high-intensity care of neurologically devastated survivors presents an immense burden to healthcare systems, patients' families, and society in general. 251,252 To limit this burden, clinical factors and diagnostic tests are used to prognosticate functional outcome. With the limitation of care or withdrawal of life-sustaining therapies as a likely outcome of prognostication, studies have focused on poor long-term prognosis (vegetative state or death) based on clinical or test findings that indicate irreversible brain injury.…”
Section: Post-cardiac Arrest Prognosticationmentioning
confidence: 99%
“…The need for protracted high-intensity care of neurologically devastated survivors presents an immense burden to healthcare systems, patients' families, and society in general. 251,252 To limit this burden, clinical factors and diagnostic tests are used to prognosticate functional outcome. With the limitation of care or withdrawal of life-sustaining therapies as a likely outcome of prognostication, studies have focused on poor long-term prognosis (vegetative state or death) based on clinical or test findings that indicate irreversible brain injury.…”
Section: Post-cardiac Arrest Prognosticationmentioning
confidence: 99%
“…Protracted hospitalization for post‐OHCA patients, the majority of whom will not survive with meaningful neurologic recovery, carries considerable ethical and economic implications 16, 17. Multiple models have previously been developed with the goal of earlier outcome stratification,18, 19, 20, 21 yet all are significantly limited by invalidity in TTM populations and/or weighting toward historically unreliable arrest timing variables (eg, time to return of spontaneous circulation [ROSC]) 22.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that except in extremely rare situations, resuscitation in these patients is futile. 10,11 In the age group over 70 years, only one of our patients survived out of 23 cardiac arrests and he was discharged to his local hospital in a persistent vegetative state. None survived to discharge in 77 elderly hospital patients reviewed by Taffet 12 in 1988.…”
Section: Discussionmentioning
confidence: 88%
“…At the same time, it is becoming clear that a blanket policy for the provision of CPR for all patients may not be appropriate and that a more flexible approach may be justified. It is becoming clear that certain groups of patients should not be resuscitated, such as those patients brought into the Emergency Department after failed resuscitation in the community, 11 or those with metastatic cancer. 17 It may be reasonable for some groups of patients to be subjected to modified resuscitation, e.g., defibrillation, only in the case of a witnessed cardiac arrest in a hospitalized, debilitated, elderly patient.…”
Section: Discussionmentioning
confidence: 99%